GOOD CORPORATE GOVERNANCE PENYELENGGARA PENDIDIKAN DALAM PERSPEKTIF AGENCY TEORY - Martinus Sony Erstiawan (Majalah Ekonomi, 2021)
Schools as instruction suppliers can take advantage of the standards of great corporate administration as an exertion to move forward the quality of the institution. The utilize of the standards of straightforwardness, responsibility, obligation, autonomy, decency (uniformity and reasonableness) must be carried out in a feasible way, displayed to partners. Utilization of the standards of great corporate administration can be utilized as a premise for input from principals/school approach creators (instruction suppliers) which of course can be a fabric for progressing the quality of instruction, particularly in areas/areas distant from urban regions (towns) which still require more endeavors to progress quality. instruction and the quality of understudies. Whereas the organization hypothesis can minimize vital and specialist clashes where utilizing discourse, coordination and shoulder-to-shoulder strategies, endeavors ought to be made to proceed and not constrain opportunity of expression as an specialist. This research is a literature review for education providers by comparing one article with another and generating criticism, input and arguments. The focus of this research is on the use of good corporate governance in schools (education providers), so that further research can be guided by the KNKG and describe the agency theory contained in these schools.